What Teacher Confirmation Means to EFL Learners: High and Low Achievers’ Voices - Novianti, Sri; Kurniawan, Eri; Selpia, Delpani; Lutfiyana, Faza (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
One of factors leading to the success of students’ learning is interpersonal relationships between teachers and students. One indicator contributing to this relationship is communication; one of its aspects is teacher confirmation, happening in the classroom interaction. The current study aims to reveal students’ perceptions on teacher confirmation as one of elements affecting student-teacher interpersonal relationships and how teacher confirmation affects their learning. This case study involved two high school students - high achiever and low achiever - selected from their English competence judged by the English teacher. Adapting Ellis’ Teacher Confirmation Scale (2000), sequenced and open-ended interview was conducted to both students in order to collect the data. The findings show that teacher confirmation exists in the classroom interaction and is perceived by both participants. Notwithstanding, teacher confirmation does not equally give positive impacts on students’ learning in general. In conclusion, high and low achiever responds teacher confirmation in different ways, resulted from factors which have not yet been explored in this study. Examining related intervening factors and the degree to which they affect how students perceive and respond to teacher confirmation is recommended for future research.